A Tale of 2 Teachers: A Preschool Physical Activity Intervention Case Study - Howie, Erin; Brewer, A.; Dowda, M.; McIver, K.; Saunders, R.; Pate, R. (Wiley-Blackwell Publishing Inc, 2016)
BACKGROUND: Preschool settings vary greatly, and research has shown that interventions are more successful when they can be adapted to individual settings. This is a descriptive case study of how 2 teachers successfully adapted and implemented a preschool physical activity intervention. METHODS: The Study of Health and Activity in Preschool Environments (SHAPES) was a 3-year physical activity intervention. A detailed case study of 2 high-implementing teachers was conducted. Multiple data sources included accelerometry, direct observation, teacher surveys, and intervention staff field notes. RESULTS: Teacher A focused on integrating physical activity into a wide range of activities, including parent and community events. Teacher B focused on high-intensity, structured activities. Both teachers supported the intervention, worked closely with intervention staff, and operated their classroom as an autonomous unit with support from their directors. Teacher A provided an average of 31.5, 78.0, and 67.5 min of physical activity opportunity per day of observation during years 1, 2, and 3. Teacher B provided an average of 2.7, 33.5, and 73.3 minutes of physical activity opportunity per day of observation. CONCLUSION: Successful implementation of physical activity interventions may look different in different contexts; thus, interventions should allow for flexible implementation.